2015
DOI: 10.3329/sja.v13i1.24187
|View full text |Cite
|
Sign up to set email alerts
|

Crop sequences for increasing cropping intensity and productivity

Abstract: Field experiments were conducted at the Central Research Station of Bangladesh Agricultural Research Institute (BARI) for three consecutive years (2011-12, 2012-13 and 2013-14) to study the comparative agronomic performance and economic return of different cropping sequences for increasing cropping intensity and productivity. Three cropping patterns (CP1 - Transplanted Aman rice (var:Binadhan-7)– Mustard (var:BARISarisha-14)– Boro rice (var:BRRIdhan-28)– Transplanted Aus rice (var:Parija), CP2 - T. aman rice –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 7 publications
9
28
0
Order By: Relevance
“…Inclusion of mustard in rabi season and T.Aus in kharif-1 season in existing cropping pattern increased total productivity by 92 % compared to farmers' practice. These results are in agreement with Mondal et al (2015). They reported that total productivity increased by 67 % over farmers' practice.…”
Section: Rice Equivalent Yieldsupporting
confidence: 83%
See 2 more Smart Citations
“…Inclusion of mustard in rabi season and T.Aus in kharif-1 season in existing cropping pattern increased total productivity by 92 % compared to farmers' practice. These results are in agreement with Mondal et al (2015). They reported that total productivity increased by 67 % over farmers' practice.…”
Section: Rice Equivalent Yieldsupporting
confidence: 83%
“…The marginal benefit cost ratio (MBCR) also showed that inclusion of mustard and T.Aus in the existing pattern might be profitable and acceptable to the farmers. These results are supported by Mondal et al (2015). They reported that inclusion of T.Aus, potato, mustard and mungbean in the existing pattern were profitable and acceptable to the farmers and grown successfully one after another in sequence of one year cycle.…”
Section: Cost and Return Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…In these cropping patterns, land remains fallow for more or less 80 days after Boro rice harvest (Haque et al, 2001;Khan et al, 2004). Four crops based cropping patterns (Boro rice-T. Aus rice-T. Aman rice-Mustard or Boro rice-Jute-T. Aman rice-Mustard) require 345-351 days excluding seedling age of rice crop and the land area remains fallow only for 14-20 days in a year (Mondol et al, 2015;Rahman et al, 2015). During the turnover period between Boro rice harvest and succeeding crop cultivation, the land remains fallow for 14-80 days.…”
Section: Introductionmentioning
confidence: 99%
“…Oilseed and pulse are the important group of crops in calcareous soils which are mostly grown in rabi (winter) and kharif-I (summer) season but area of those crops decreased due to increasing cultivation of irrigated boro (long durated) rice (FRG, 2012). Recently, developments of short duration varities of mustard, mungbean and rice have been created opportunity to accommodate three or more crops in same piece of land in a year (Mondal et al, 2015). Mustard (Brassica napus), mungbean (Vigna radiata) and T. aman rice (Oryza sativa L.) grown sequentially in an annual rotation constitute a mustard-mungbean-T. aman cropping system (Iqbal et al, 1990).…”
Section: Introductionmentioning
confidence: 99%